Tell the truth : honesty is your most powerful marketing tool. - Unerman, Sue, ....-; Salem Baskin, Jonathan, ....- (Dallas : Benbella books, 2012)
Truth is a powerful marketing tool--and really the only way to promote a message and brand effectively. Truth in advertising has long been something to ignore, or at least downplay. The role of advertising has been to position and manipulate brands to convince consumers that they're imbued with qualities they don't necessarily possess, or presume to tell them which ones matter. It worked when the brand's voice was the only voice, but with the rise of social media that era is over. Marketers have focused their messages on entertainment, creating funny or engaging campaigns that win awards but don't always sell products. Consumers determine what's true, and smart companies have realized that every communications medium can and will be used to contribute to those conclusions. In Tell the Truth, Jonathan Salem Baskin and Sue Unerman look at the content and context of marketing communications. They provide the research of hundreds of companies and in-depth case studies on more than 50 global brands to show us that truthful brands deliver sales, profits, and sustainable relationships. Truth yields true competitive advantage.
Keywords: Eerlijkheid; Marketing